Effects of High-Frequency Repetitive Transcranial Magnetic Stimulation Combined with Task-Oriented Mirror Therapy Training on Hand Rehabilitation of Acute Stroke Patients - Kim, Jinhong (Med Sci Monit, 2018)
BACKGROUND: Impairments of hand function make it difficult to perform daily life activities and to return to work. The aim of this study was to investigate the effect of high-frequency repetitive transcranial magnetic stimulation (HF-rTMS) combined with task-oriented mirror therapy (TOMT) on hand rehabilitation in acute stroke patients. MATERIAL/METHODS: Twenty subacute stroke patients in the initial stages (<3 months) participated in the study. Subjects were allocated to 2 groups: the experimental group received HF-rTMS + TOMT and the control group received HF-rTMS. TOMT training was conducted in 10 sessions over 2 weeks for 30 min. rTMS was applied at a 20 Hz frequency over the hand motor area in the cortex of the affected hemisphere for 15 min. Outcomes, including motor-evoked potential (MEP), pinch grip, hand grip, and box and block test, were measured before and after training. RESULTS: Significant improvements in the MEP and hand function variables were observed in both groups (p<0.05). In particular, hand functions (pinch grip and box and block test) were significantly different between the 2 groups (p<0.05). CONCLUSIONS: HF-rTMS combined with TOMT had a positive effect on hand function and can be used for the rehabilitation of precise hand movements in acute stroke patients.